2004
DOI: 10.1007/s11837-004-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

The non-destructive and nano-microstructural characterization of thermal-barrier coatings

Abstract: The durability of thermal barrier coatings (TBCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Associating this crack diameter with the (apparent) interfacial fracture toughness of the TBC system results in the aged coatings having higher interfa cial fracture toughness than the as-coated material. This is in contradiction to the typically observed behavior of TBCs in thermal and thermomechanical tests and in ser vice [23,25,26]. Careful examination of the crack pattern of indentation-induced crack systems revealed that the crack paths changed due to aging.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Associating this crack diameter with the (apparent) interfacial fracture toughness of the TBC system results in the aged coatings having higher interfa cial fracture toughness than the as-coated material. This is in contradiction to the typically observed behavior of TBCs in thermal and thermomechanical tests and in ser vice [23,25,26]. Careful examination of the crack pattern of indentation-induced crack systems revealed that the crack paths changed due to aging.…”
Section: Discussioncontrasting
confidence: 78%
“…9 (dashed lines). This implies that that the interfacial tough ness increases as the system ages and is at variance to the common understanding of the evolution of material prop erties of TBCs [8,23,24]. Moreover, it appears as the response can be divided into two cases: ''small" and ''large" maximum indentation force.…”
Section: Debonding Cracksmentioning
confidence: 96%
“…tion to what is observed in durability experiments and in field tests of thermal barrier coatings [5,13].…”
Section: Numerical Modelmentioning
confidence: 58%
“…The integrity of thermal barrier coatings (TBCs) composed typically of yttria-stabilized zirconia, their failure mechanisms, non-destructive evaluation, life prediction, and life-remaining assessment have been a critical and active research topic with application in gas turbine industries. While Padture et al, 11 Clarke et al, 12 and Sohn et al, 13 have contributed to the understanding of failure mechanisms and non-destructive evaluation techniques for TBCs, concepts of fuel-fl exible energy generation warrants sustained research related to TBCs and other protective coatings.…”
Section: Desaimentioning
confidence: 99%